Green Accounting Concept Based on University Social Responsibility as A Form of University Environmental Awareness - Muh Akil Rahman; Sumarlin Sumarlin; Sari Fatimah Mus; Murtiadi Awaluddin; Rulyanti Susi Wardhani (Integrated Journal of Business and Economics (IJBE), 2019)
Environmental issues are not a new issue, environmental degradation and social gaps in the environment are a matter of great concern. This study aimed to analyze the form of environmental responsibility and how the application of Green Accounting concept in a university. This qualitative research used phenomenology approach with Interpretative Phenomenological Analysis technique where the research locations were in UIN Alauddin Makassar and Hasanuddin University Makassar. Data source was primary data obtained through interview and also supported by other secondary data. The method of data analysis was constructing research conclusion by abstracting empirical data collected from the field. Findings of this study revealed that the awareness of UIN Alauddin Makassar to the environment is still inadequate and not fulfil the expectations of the campus community that is different from the responsibility of Hasanuddin University Makassar which has been considered quite responsible with the existence of various environmental conservation programs. Green Accounting concept that can be seen from environmental concerns and environmental involvement in these two universities is also very different especially in terms of building management awareness, cost availability and environmental compliance studies. As for the reporting and environmental audit, both UIN Alauddin Makassar and Hasanuddin University Makassar has not been conducted until now.